Evidence for an [eta] c(1S) π - resonance in B0→[eta] c(1S)K+ π - decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (The European physical journal. C, Particles and fields, 2018)
A Dalitz plot analysis of B0→ηc(1S)K+π−B0→ηc(1S)K+π−{B ^0} \!→ η _c(1S) {K ^+} {{π } ^-} decays is performed using data samples of pp collisions collected with the LHCb LHCb \text{ LHCb } detector at centre-of-mass energies of s√=7, 8s=7, 8{\sqrt{s}} =7,~8 and 13TeV13TeV13{\,TeV} , corresponding to a total integrated luminosity of 4.7 fb −14.7 fb −14.7 \,\text{ fb }^{-1} . A satisfactory description of the data is obtained when including a contribution representing an exotic ηc(1S)π−ηc(1S)π−η _c(1S) π ^- resonant state. The significance of this exotic resonance is more than three standard deviations, while its mass and width are 4096±20 +18−22MeV4096±20 −22+18MeV4096 ± 20~^{+18}_{-22} \,MeV and 152±58 +60−35MeV152±58 −35+60MeV152 ± 58~^{+60}_{-35} \,MeV , respectively. The spin-parity assignments JP=0+JP=0+J^P=0^+ and JP=1−JP=1−J^{P}=1^- are both consistent with the data. In addition, the first measurement of the B0→ηc(1S)K+π−B0→ηc(1S)K+π−{B ^0} \!→ η _c(1S) {K ^+} {{π } ^-} branching fraction is performed and gives B(B0→ηc(1S)K+π−)=(5.73±0.24±0.13±0.66)×10−4,B(B0→ηc(1S)K+π−)=(5.73±0.24±0.13±0.66)×10−4,\begin{aligned} \displaystyle \mathcal {B}({B ^0} \!→ η _c(1S) {K ^+} {{π } ^-} ) = (5.73 ± 0.24 ± 0.13 ± 0.66) × 10^{-4}, \end{aligned}where the first uncertainty is statistical, the second systematic, and the third is due to limited knowledge of external branching fractions.
Im Titel sind "+", "-" und "0" hochgestellt, "c" ist tiefgestellt
Im Titel ist "eta" als griechischer Buchstabe dargestellt
LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, R. Kopecna, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, M. Stahl, S. Stemmle, J. van Tilburg, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 12.06.2019